Influence of Changes to the Regulations on the Term of Village Head on Village Development - Muhammad Yusuf; Bachrul Amiq (NOVUM : JURNAL HUKUM, 2025)
The regulation of the term of office of village heads in Indonesia has undergone frequent changes, affecting the dynamics of village governance and development. The latest regulation, Law No. 3 of 2024, stipulates in Article 39 that a village head serves for 8 years and may be re-elected once, contrasting with the previous provision of 6 years with the possibility of two re-elections. This regulatory change potentially influences the continuity and effectiveness of village development, in which the village head plays a central role, particularly in managing village finances and assets. This study aims to examine the impact of the extended term of office on village development and community participation in two villages: Munggugianti and Sirnoboyo in Benjeng District, Gresik Regency. Using an empirical juridical method, the research applies a socio-legal approach through interviews, observations, and documentation. The findings indicate that a longer term of office provides better continuity in development planning and execution, allowing village heads to implement medium to long-term programs more effectively. However, challenges remain in ensuring community participation, which varies depending on public awareness and socialization efforts. In both villages, development progress shows improvement post-regulatory change, although community involvement is still not optimal and sometimes not aligned with the expectations of participatory governance. The study recommends strengthening community legal awareness, increasing transparency in village governance, and institutionalizing development planning mechanisms that actively involve the community regardless of leadership changes.